Pendidikan Karakter di Pesantren: Studi Kasus di Pondok Pesantren Cipari Kabupaten Garut - Nuraly Masum Aprily (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2019)
This research described the implementation of character education in Cipari Islamic Boarding School in Garut City that involved 1 Kyai, 1 Ustadz, and 2 santri. The main problem of this research was: How was the implementation of character education in the Cipari Islamic Boarding School in Garut City? In detail, the main problems was described in the form of research questions as follows: 1) Why was character education carried out in Cipari boarding schools? 2) How was the implementation of character education in the Cipari boarding school in Garut City? 3) What factors influence the implementation of character education in the Cipari boarding school in Garut City? This reseacrh method was a case study with a qualitative approach. The data was collected through observation, interviews, documentation and literature studies. Data was analyzed in several stages, namely: organizing data, describing it into units, synthesizing, arranging into patterns, choosing the important one to analysed and making the conclusions. The findings of this study indicated that there were five reasons underlying Cipari boarding schools carrying out character education to their students; Cipari boarding schools did not have a written program on character education but Cipari boarding schools implemented it through the application of rules and sanctions (nidzomul ma'had), habituation, reward, and a 24-hour education system, source of value, and evaluation; and there were two factors that influenced the implementation of character education in Cipari boarding schools, namely supporting and inhibiting factors.